Inequity in the distribution of human resources for health at health care services in four Peruvian regions - Moscoso Rojas, Betsy (2015)
Background: The density of Human Resources for Health (HRH) at Peru has exceeded the threshold set by WHO to ensure coverage of health services, which is 25 per 10 000 population. However this national average could masks regionally HRH densities that could be below the stipulated threshold, particularly in poorest areas. As a result it is necessary to study the existence of possible inequities in the distribution HRH inside the regions. Inequity must be understood as the unnecessary, avoidable, and unjustified lack of HRH. Objectives: To determine inequities in the distribution of HRH at health care services of four poor regions of Peru (Cajamarca, Loreto, Apurimac and San Martin). Design: Cross sectional descriptive study. Institution: Dirección General de Gestión de Desarrollo de Recursos Humanos of Ministry of Health. Methods: Density of HRH for each region was calculated. In order to evaluate inequity, Gini index was calculated for the regional settings and Theil T Index for provincial settings. Results: HRH densities in 3 of the 4 regions were below the minimum stipulated by WHO. Gini index found were Cajamarca 0.175, Loreto 0.157, Apurimac 0.372 and San Martin 0.146 indicating a tendency to equity. Meanwhile, in intra-regional analysis, Theil T index showed that a significant number of provinces had good distribution of HRH. Conclusions: Despite low density of HRH in most regions studied, HRH distribution showed a trend towards equity.